APPLICATION OF THE TECHNOLOGY ACCEPTANCE MODEL TO CHAT GPT TO MEASURE THE CRITICAL THINKING POWER OF UIN SUNAN AMPEL SURABAYA STUDENTS - Fadholi, M. Annur Fuad (MULTITEK INDONESIA, 2025)
Advances in artificial intelligence (AI) have made a big impact in the field of education, one of which is through the use of ChatGPT from OpenAI. This technology has the potential to improve the learning process, but also poses risks such as plagiarism and reduced student accountability. This study aims to determine the effect of ChatGPT on critical thinking and decision-making skills by students in their daily learning on campus. The method used is quantitative method by distributing questionnaires to active undergraduate students of UIN Sunan Ampel Surabaya using purposive random sampling technique. Data analysis was carried out using the SEM method using a tool to process data, namely SmartPLS V4 and the Technology Acceptance Model (TAM) theory. The results showed that the use of ChatGPT had a positive effect on increasing critical thinking, with the mediating variable of Decision Making and the variables of Actual Use, Behavioral Intention to Use, Perceived Usefulness, and Perceived Ease of Use as the determining factors. The results of this study are expected to contribute to understanding student behavior related to the use of ChatGPT and its impact on scientific reasoning and decision making.